Mapeamento de áreas úmidas e banhados na microbacia do Rio Amandaú, região noroeste do Rio Grande do Sul - Meller, Juliana (2011)
The wetlands are one of the world s most productive places, with high rates of biological diversity and also highly impacted. In this context, this project was aimed at mapping the Wetlands Ecosystems present in the soil moisture in the watershed of the Amandau River (Watershed U30), using orbital images and clinographic terrain maps. This research was structured in six different steps: first: choosing the area of study; second, searching for theorical background; third, cartographic production, using the computer program SPRING 5.1.5; forth, field research; fifth, creation of a data bank (Access 2007), sixth, analyzes of data and consideration of the results comparing the the Environmental Legislation. It was found that the clinographic maps generated from the Granell-Pérez (slope from 0 to 3%) purposes became the best available cartographic material for the identification of the humid areas and maping of 82 spots in 16 locations. The Wetland Ecosystem was identified in 62,20% of the mapped terrains, 68,62% showing amendments from its natural characteristics provoked by the drainage practice. It was found that 84,31% is used for raising cattle, 39,21% for damming and 15,68% for agriculture. In the biggest part of the watershed (60,98%), the riparian vegetation of the APP (permanent preservation area) was considered inexistent or inexpressive (3,24 meter of average). Regarding the wetland ecosystem, 100% of the areas do not observe the use of APP according to the Environmental Legislation (50 meters). The erosion and siltation of the hydrical resources are in 84,15% of the areas. The basic mapping of the wetlands in moisture soil, using the clinographic map, was fundamental to consider the first steps to the conservation of the watershed ecosystem. Generally, it was understood that the degradation level of the wetlands ecosystem is high and the Environmental Legislation is not being observed. Actions to control the environmental impacts are generated by the diverse activities in rural areas and the recovery of natural environments, are necessary and urgent.